1997
DOI: 10.1161/01.cir.96.11.3913
|View full text |Cite
|
Sign up to set email alerts
|

QT Dispersion Is Determined by the Extent of Viable Myocardium in Patients With Chronic Q-Wave Myocardial Infarction

Abstract: QT dispersion is determined by the amount of viable myocardium in the infarct region and may serve as a novel, rapidly available marker of substantial viability in the infarct region of patients with chronic Q-wave myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 26 publications
6
39
1
1
Order By: Relevance
“…The inclusion of hypertensive patients in the control group may have also been responsible for reducing the differences between the groups. In addi-Vol 43 No 5 tion, the present study only provided one point data in each patient with chronic myocardial infarction. Accordingly, longitudinal studies are needed to establish the changes in QTc dispersion over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inclusion of hypertensive patients in the control group may have also been responsible for reducing the differences between the groups. In addi-Vol 43 No 5 tion, the present study only provided one point data in each patient with chronic myocardial infarction. Accordingly, longitudinal studies are needed to establish the changes in QTc dispersion over time.…”
Section: Discussionmentioning
confidence: 99%
“…4) Gabrielli, et al 20) reported that QT dispersion was increased soon after infarction and then decreased again after ten days, although not all patients showed improvement. Schneider, et al 5) studied patients in the chronic phase of infarction and found that QT dispersion was decreased in patients who showed improvement in wall motion after four months, while it showed little change in those without improvement in wall motion, suggesting that QT dispersion could be used as an index of cardiac function in chronic myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some discrepancy between ECG location of Q waves, and echocardiographic and scintigraphic studies in the regional analysis may be due to anatomic misregistration of segments. Whether or not other aspects of the ECG are helpful in predicting viability, particularly QT dispersion, 15 were not explored in this investigation, mostly to assess the application of a simple parameter that can be used by any clinician at the bedside in the evaluation of myocardial viability.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Various ECG parameters at rest or during exercise were applied to assess myocardial viability or recovery of functionfor example, QT dispersion and T-wave normalization 9,10 -in a population with severely diseased but mostly patent arteries. The extent of Q waves in the resting ECG was used to assess a QRS score (Selvester Score) to predict infarct size and LV function after myocardial infarction (MI).…”
Section: Introductionmentioning
confidence: 99%